Resources for controlling tuberculosis in Malawi - Harries Anthony D.; Kwanjana John H.; Hargreaves Nicola J.; Van Gorkom Jeroen; Salaniponi Felix M.L (The World Health Organization, 2001)
OBJECTIVE: To document resources for controlling tuberculosis (TB) in Malawi. METHODS: We performed a countrywide study of all 43 hospitals (3 central, 22 district and 18 mission) which register and treat patients with TB. To collect data for 1998 on the TB-related workload, diagnostic facilities, programme staff and treatment facilities, we used laboratory, radiographic and TB registers, conducted interviews and visited hospital facilities. FINDINGS: The data show that in 1998, 88 257 TB suspects/patients contributed approximately 230 000 sputum specimens for smear microscopy, 55 667 chest X-rays were performed and 23 285 patients were registered for TB treatment. There were 86 trained laboratory personnel, 44 radiographers and 83 TB programme staff. Of these, about 40% had periods of illness during 1998. Approximately 20% of the microscopes and X-ray machines were broken. Some 16% of the hospital beds were designated for TB patients in special wards, but even so, the occupancy of beds in TB wards exceeded 100%. Although stocks of anti-TB drugs were good, there was a shortage of full-time TB ward nurses and 50% of district hospitals conducted no TB ward rounds. In general, there was a shortage of facilities for managing associated HIV-related disease; central hospitals, in particular, were underresourced. CONCLUSION: Malawi needs better planning to utilize its manpower and should consider cross-training hospital personnel. The equipment needs regular maintenance, and more attention should be paid to HIV-related illness. The policies of decentralizing resources to the periphery and increasing diagnostic and case-holding resources for central hospitals should be continued.